2018
DOI: 10.1371/journal.pone.0206039
|View full text |Cite
|
Sign up to set email alerts
|

Schema therapy for borderline personality disorder: A qualitative study of patients’ perceptions

Abstract: Schema therapy (ST) has been found to be effective in the treatment of borderline personality disorder (BPD). However very little is known about how the therapy is experienced by individuals with BPD including which specific elements of ST are helpful or unhelpful from their perspectives. The aim of this study is to explore BPD patients’ experiences of receiving ST, in intensive group or combined group-individual format. Qualitative data were collected through semi-structured interviews with 36 individuals wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 43 publications
1
13
0
4
Order By: Relevance
“…Other effects included an improvement in problem solving skills and physical well-being. In the study by Tan et al ( 17 ), patients with BPD receiving ST also reported broad therapeutic gains in various areas of life, while perceiving IR and other experiential techniques as emotionally confronting. The majority of the participants in our trial estimated the benefits of IR to be higher than the costs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other effects included an improvement in problem solving skills and physical well-being. In the study by Tan et al ( 17 ), patients with BPD receiving ST also reported broad therapeutic gains in various areas of life, while perceiving IR and other experiential techniques as emotionally confronting. The majority of the participants in our trial estimated the benefits of IR to be higher than the costs.…”
Section: Discussionmentioning
confidence: 99%
“…De Klerk et al ( 15 ) interviewed patients with PDs (BPD excluded) about their experiences with ST in general, and Ten Napel-Schutz et al ( 16 ) interviewed patients with PDs (BPD excluded) about their experiences with imagery (“safe place” and “diagnostic imagery”). There is one study that interviewed patients with BPD about their experiences with ST ( 17 ), finding that these patients experienced the experiential techniques (including IR) used during ST as confronting, but important. However, detailed information on how BPD patients perceived IR is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Early intervention programs are effective [ 4 ] and cost saving versus the later financial impact of the psychopathology of the individuals who could have been helped by the program [ 5 ]. Schema therapy is a well-established cognitive behavioral approach with a firm evidence base for both theory and practice [ 104 ] with acceptability of specific techniques from the perspective of patients [ 105 , 106 ] and therapists [ 107 ]. This large-scale qualitative study showed that Good Enough Parenting, the schema therapy early intervention and parenting program, has considerable acceptability to the end user participants.…”
Section: Discussionmentioning
confidence: 99%
“…The method allows therapists to help adolescents move on from difficult incidents and choose newer and healthier ways of doing activities. As adolescents focus on their peers and accept their responses more than those of their parents' or healthcare specialists', they could benefit from group therapy better than adults (19,20).…”
Section: Internalizing and Externalizing Behaviors Often Emerge During Adolescence And Early Interventions Couldmentioning
confidence: 99%